Evaluation of Platelet-Rich Plasma by means of PRGF®-Endoret® protocol in leukemia cats: PDGF-BB and TGF-ß1 valuation - Miguel-Pastor, Laura; Satué, Katy; Chicharro, Deborah; Peláez, Pau; Torres-Torrillas, Marta; Carrillo, José M.; Cerón, José J.; Sopena, Joaquín J.; Rubio, Mónica (Frontiers in Veterinary Science, 2023)
Feline leukemia virus (FeLV) is a chronic disease that leads to the weakening of a cat's immune system. Platelet-rich plasma (PRP) offers therapeutic effects for multiple diseases, the use of PRP and growth factor (GFs) determination could be an alternative treatment to improve the quality of life in these patients. The objectives of this study were to determine and compare the concentration of platelets (PLTs), red blood cells (RBCs) and white blood cells (WBCs) between samples of whole blood (WB), PRP and platelet-poor plasma (PPP) fractions, and to evaluate the concentration of platelet-derived growth factor BB (PDGF-BB) and transforming growth factor β1 (TGF-β1) in both fractions in FeLV cats using a PRGF®-Endoret® protocol previously standardized in this species. WB was collected from 11 asymptomatic FeLV-positive cats. PRP and PPP was obtained following PRGF®-Endoret® technology according to centrifugation at 265g for 10min. Cellular components, RBCs, WBCs, PLTs, and the PDGF-BB and TGF-β1 concentrations in PRP and PPP fractions were determined. PLT in the PRP fraction was statistically higher than WB and PPP fraction, with no statistical differences between WB and PPP. PLT concentration increased 1.4 times in PRP fraction compared to WB. MPV did not differ significantly between the WB, PRP and PPP fractions. Compared to WB, the absolute numbers of RBCs and WBCs were decreased by 99% and more than 95% in the PRP and PPP fractions, respectively. TGF-ß1 concentrations increased in PRP versus PPP, with no changes in PDGF-BB. Based on the degree of PLT enrichment and the absence of RBCs and WBCs, this blood product could be classified as a Pure Platelet-Rich Plasma (P-PRP). The presence of GFs in PRP and PPP samples suggests that the PRGF®-Endoret® methodology is suitable for obtaining PRP in FeLV cats, despite future studies are necessary to optimize the technique, standardize the results and assess clinical efficacy.